2013
DOI: 10.1159/000355101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adenomyosis on In Vitro Fertilization/Intracytoplasmic Sperm Injection Outcomes in Infertile Women: A Retrospective Cohort Study

Abstract: Aims: To study the effect of adenomyosis on in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) outcomes in infertile patients. Methods: We performed a retrospective, database-searched cohort study based on 10,268 patients undergoing controlled ovarian hyperstimulation and IVF/ICSI between 2009 and 2011 in our unit. Adenomyosis was diagnosed by transvaginal ultrasound. A high-quality matched cohort study with strict inclusion criteria was conducted. We compared the basic characteristics and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 15 publications
(18 reference statements)
2
57
1
4
Order By: Relevance
“…Also, our findings emphasize the importance of using combined treatment for infertility patients affected by endometriosis of different stages and in the case of coexisting adenomyosis. In contrast, there is evidence that adenomyosis has a negative impact on the pregnancy outcome [34]. However, the results of our study suggested that the pregnancy rate was not affected by the higher frequency of adenomyosis in the patients with more severe stages of endometriosis compared to the patients with minimal to mild endometriosis.…”
Section: Discussioncontrasting
confidence: 89%
“…Also, our findings emphasize the importance of using combined treatment for infertility patients affected by endometriosis of different stages and in the case of coexisting adenomyosis. In contrast, there is evidence that adenomyosis has a negative impact on the pregnancy outcome [34]. However, the results of our study suggested that the pregnancy rate was not affected by the higher frequency of adenomyosis in the patients with more severe stages of endometriosis compared to the patients with minimal to mild endometriosis.…”
Section: Discussioncontrasting
confidence: 89%
“…Diagnostic criteria for AD were based on MRI findings of abnormal myometrial and JZ thickness in two IVF studies: Ballester, 2012 ; Maubon, 2010 . TVS in nine IVF / ICSI studies: Costello, 2011 ; Chiang, 1999 ; Martinez‐Conejero, 2011 ; Mijatovic, 2010 ; Salim, 2012 ; Thalluri, 2012 ; Youm, 2011 ; Yan, 2014 ; Benaglia, 2014 . In studies of women scheduled for endometriosis surgery, diagnosis was based on MRI in one study: Landi 2008 , TVS in two: Stepniewska, 2010 ; Soriano, 2016 and both techniques in two: Darai, 2010 ; Ferrero, 2009 .…”
Section: Methodsmentioning
confidence: 99%
“…The effect of AD on IVF/intracytoplasmic sperm injection (ICSI) outcome has been described in a total of 11 studies. Four studies were case–control studies , and seven cohort studies . Additionally, the effect of AD on pregnancy rate (PR) (both spontaneous and ART pregnancy) after surgery for rectovaginal and colorectal endometriosis is described in five trials .…”
Section: Effect Of Adenomyosis On Reproductive Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasound examination was done by the same ultrasonographer, using the same ultrasound equipment (Hitachi EUB-2000, Japan). The serum FSH, luteinizing hormone and E 2 levels were determined by the electrochemiluminescence immunoassay (Roche, Basel, Switzerland) on day 4 of the menses for all treated women [20]. Information about sperm concentration, sperm motility and sperm morphological features of the partners was also recorded (WLJY-9000 semen analyzer, China).…”
Section: Methodsmentioning
confidence: 99%